Decomposition of the gender wage gap in Portugal, 1998-2007: the evidence of gender discrimination - Figueiredo, M. C. T.; Botelho, M.C. (Portuguese Journal of Social Science, 2013)
The purpose of this paper is to analyse the gender wage gap in Portugal by applying the counterfactual decomposition method of Machado and Mata (2005). In order to obtain a measure for wage discrimination at different quantiles, wage function estimation is based on quantile regression analysis (Koenker and Basset, 1978), using datasets from the Inquérito ao Emprego, Portuguese Labour Force Survey (IELFS) of 1998 and 2007. The decomposition of gender wage inequality shows potential wage discrimination by gender due to the differences in the returns of working men's and women's characteristics. This discrimination increases across the whole distribution, for both 1998 and 2007. Although the differences in the working men's and women's characteristics reduced, the results show empirical evidence of the persistence of the discrimination effect in 2007 – at the same level. In addition, Oaxaca-Blinder's standard decomposition approach, developed in 1973, was applied. The results confirm that the average gender wage gap does not reflect the reality observed throughout the wage distribution, inasmuch as it overestimates what happens in lower-level quantiles and underestimates those of the higher levels.